Research on the Innovation and Protection Mechanism of Intangible Cultural Heritage Tourism Products under the "Belt And Road" Initiative: A Multicultural Integration Perspective - Wanwan, Liu; Haris, Mohamad Fitri Bin Mohamad (Journal of Posthumanism, 2025)
This study focuses on the innovative development and protection mechanism of intangible cultural heritage tourism products under the background of the "Belt and Road" initiative. Through a mixed research method, a case study of the intangible cultural heritage tourism product development model in typical areas along the route was conducted, and an integrated model of intangible cultural heritage tourism product innovation and protection was constructed based on questionnaire survey and in-depth interview data. The study found that the innovation of intangible cultural heritage tourism products needs to balance cultural authenticity and market demand, and an effective protection mechanism should include four dimensions: government guidance, corporate participation, community co-construction, and tourist education. This study proposes a "symbiotic development" theoretical framework to provide new ideas for the sustainable development of intangible cultural heritage tourism in cross-cultural exchanges, and at the same time provide policy recommendations for the coordinated development of cultural heritage protection and tourism development under the "Belt and Road" initiative.